Influence of nanobiocomposites on the exopo lysac charide matrix of Bacillus strains - Safronova, L.A.; Voychuk, S.I.; Brovarska, O.S. (Доповіді НАН України, 2020)
The effect of nanobiocomposites of carrageenan and galactomannan — perspective prebiotics on the formation of the extracellular polysaccharide complexes of Bacillus amyloliquefaciens subsp. plantarum UCM B-5139 and UCM B-5140 probiotic strains is studied. Analysis of data showed that bacterial strains had differences in the content of various sugar residues within their exopolysaccharide matrices. Both compounds, carrageenan and galactomannan, and their nanocomposites showed a potency to change the content of the extracellular matrix of bacilli probiotic cells. The effect of these compounds depended, presumably, on the natural structural properties of polysaccharides of these strains. However, the synthesis of extracellular polysaccharides by Bacillus probiotic strains was not bloc ked in the presence of the investigated nanocomposites. The obtained results indicate the possible dual (direct and indirect) action of polysaccharides and their nanocomposites in case of their use as the prebiotic components of synbiotic preparations: through the direct biologi cal action on the properties of the mammalian epithelial cells or gut microflora, and indirectly through the changes of properties of the extracellular polysaccharide matrix of probiotic strains.